2020
DOI: 10.21203/rs.3.rs-103515/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face Mask Utilization in the Era of COVID-19: Nigeria Experience

Abstract: Background: The use of face masks has been accepted and recommended globally as a tool for COVID-19 protection. The government of Nigeria made wearing of face masks compulsory in public places. However, no evidence has shown user compliance or knowledge. This study investigated the knowledge and utilization of face masks among the Nigerian population. Methods: This was a web-based cross-sectional survey conducted from July 2 to August 28, 2020 using a convenience sampling technique. This was in adherence to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Respondents with a post-graduate or graduate degree had a considerably higher practice score than those with only secondary education, these results are in accordance with Egbi et al ( 2020) [43] . In contrast to the findings of this investigation, the study of Edet et al ( 2020) [44] found that age was strongly correlated with COVID-19-related behaviors. In their study Kamal et al (2021) [45] found a significant relationship between practice scores and age and place of residence, but Adesegun et al ( 2020) [46] found no significant differences in respondents' practice levels based on age, occupation, marital status, degree of education, or place of residence.…”
Section: After Childbirth Noncontrasting
confidence: 99%
See 1 more Smart Citation
“…Respondents with a post-graduate or graduate degree had a considerably higher practice score than those with only secondary education, these results are in accordance with Egbi et al ( 2020) [43] . In contrast to the findings of this investigation, the study of Edet et al ( 2020) [44] found that age was strongly correlated with COVID-19-related behaviors. In their study Kamal et al (2021) [45] found a significant relationship between practice scores and age and place of residence, but Adesegun et al ( 2020) [46] found no significant differences in respondents' practice levels based on age, occupation, marital status, degree of education, or place of residence.…”
Section: After Childbirth Noncontrasting
confidence: 99%
“…In their study Kamal et al (2021) [45] found a significant relationship between practice scores and age and place of residence, but Adesegun et al ( 2020) [46] found no significant differences in respondents' practice levels based on age, occupation, marital status, degree of education, or place of residence. According to Edet et al ( 2020) [44] marital status was not substantially associated with COVID-19…”
Section: After Childbirth Nonmentioning
confidence: 96%